2015
DOI: 10.1111/ijau.12052
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Examination of Auditors' Willingness to Relocate in Public Accounting: Evidence from Hong Kong and the United States

Abstract: This empirical study examines the determinants of factors influencing auditors' willingness to relocate nationally and internationally in public accounting on two cultural dimensions. This is the first study in the cross-cultural literature to examine this under-researched issue. A theoretical model is developed from family systems theory and social role theory. Logistic regression models (Models 1-16) are performed. While a cultural difference between auditors in the United States (US) and in Hong Kong (HK) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
(233 reference statements)
0
2
0
Order By: Relevance
“…It became evident that the complications of worldwide trade and commercial activities led to the consideration of the factor that impacts the shape of strategy with respect to accounting: the market economy itself. Therefore, with the adoption of those international standards of accounting and auditing comes economic improvement through the attraction of foreign investment, the development of stock markets and the achieving of the prerequisite required to secure the loans provided by financial bodies, such as the WB and the IMF (Law et al 2016;Bondar 2018;El-Helaly et al 2020). However, Boolaky and Omoteso (2016) and Boolaky and Soobaroyen (2017) discovered controversial results in that they showed a significant and positive relationship between the implementation of ISAs and the extent of stock exchange capitalisation.…”
Section: The Influence Of the Economy And The Stock Marketmentioning
confidence: 99%
“…It became evident that the complications of worldwide trade and commercial activities led to the consideration of the factor that impacts the shape of strategy with respect to accounting: the market economy itself. Therefore, with the adoption of those international standards of accounting and auditing comes economic improvement through the attraction of foreign investment, the development of stock markets and the achieving of the prerequisite required to secure the loans provided by financial bodies, such as the WB and the IMF (Law et al 2016;Bondar 2018;El-Helaly et al 2020). However, Boolaky and Omoteso (2016) and Boolaky and Soobaroyen (2017) discovered controversial results in that they showed a significant and positive relationship between the implementation of ISAs and the extent of stock exchange capitalisation.…”
Section: The Influence Of the Economy And The Stock Marketmentioning
confidence: 99%
“…In terms of studies revealing age and gender differences, the scientific community has confirmed age to be an influential factor for international mobility (e.g. Chen and Lin, 2014; Eby and Russel, 2000; Huber and Novotny, 2011; Law et al , 2016). Relatively old studies conducted by Adler (1986), Hill and Tillery (1992), Tharenou (2008) and Van der Velde et al (2005) revealed only moderate gender differences in international career choice preferences.…”
Section: The Extant Literature On Millennials and What (De)motivates ...mentioning
confidence: 99%